Weighting of Discriminant Mail Characteristics within Measuring System for Efficiency of Postal Transportation Services - Salava, Daniel; Pojkarová, Kateřina; Švadlenka, Libor (Kaunas University of Technology, 2016)
This paper is focused on the role and assessment of weighting parameters for discriminant mail characteristics within measuring system for efficiency of postal transportation services, concretely end-to-end postal services for single piece priority mail. Provision and operation of such services is measured by on-time performance evaluation of test postal items flows with key measured parameter of transit time. The results come out from modelling of measurement system for postal transport network efficiency in proportion to real postal traffic flows with particular discriminant characteristics of test items. Distribution of mail flows within geographical and other stratificational characteristics according to disjunctive set of defined subsets of test postal items must structurally correspond to characteristics of real mail flows. Process of weighting ensures compensation of difference between distribution of characteristics in measuring system in comparison with selected design basis, which is usually represented by real mail study. Assessment of calculated weighting parameters is the main objective of this paper, because they evaluate measuring system efficiency by required proportionality with design basis and could serve as base for next modelling of this system. Calculation of these parameters presumes fixed postal transportation network and domestic mail flows for various sample sizes.
Vážení rozlišujících znaků zásilek v rámci měřicího systému efektivity poštovních přepravních služeb
Keywords: transit time; priority mail; traffic flows; weighting; přepravní doba; prioritní zásilky; přepravní toky; vážení